Metabolomic and transcriptomic analyses identify external conditions and key genes underlying high levels of toxic glycoalkaloids in tubers of stress-sensitive potato cultivars - Merino, Irene; Guasca, Alexandra Olarte; Krmela, Ales; Arif, Usman; Ali, Ashfaq; Westerberg, Erik; Jalmi, Siddhi Kashinanth; Hajslova, Jana; Schulzova, Vera; Sitbon, Folke (Frontiers in Plant Science, 2023)
High levels of toxic steroidal glycoalkaloids (SGA) in potato tubers constitutes a recognized food quality problem. Tuber SGA levels vary between potato cultivars, and can increase after post-harvest stresses such as wounding and light exposure. A few cultivars, e.g. 'Magnum Bonum' and ´Lenape´, have been withdrawn from commercial sales due to excessive SGA levels during some cultivation years. However, these sudden SGA increases are diffucult to predict and their causes are not understood.To identify external and genetic factors that underlie sudden SGA increases in certain potato cultivars, we have here in a two-year study investigated ´Magnum Bonum´ and five additional table potato cultivars for their SGA levels after wounding and light exposure. Results showed that ´Magnum Bonum´ has an unusually strong SGA response to light exposure, but not to wounding, whereas 'Bintje´ displayed an opposite regulation. Levels of calystegine alkaloids were not significantly altered by treatments, implicating independent metabolic regulation of SGA and calystegine levels also under conditions of high SGA accumulation. Metabolomic and transcriptomic analyses identified a small number of key genes whose expression correlated with SGA differences between cultivars. Overexpression of two key genes in transgenic low-SGA potato cultivars increased their leaf SGA levels significantly.The results show that a strong response to light can underlie the SGA peaks that occasionally occur in certain potato cultivars, and indicate that a between-cultivar variation in the expression of single SGA key genes can account for cultivar SGA differerences. We propose that current attempts to mitigate the SGA hazard will benefit from an increased consideration of cultivar-dependent SGA responses to post-harvest conditions, in particular light exposure. The identified key SGA genes can now be used as a molecular tool in this work.